2018
DOI: 10.11591/ijere.v7i2.13141
|View full text |Cite
|
Sign up to set email alerts
|

Democratic Perception and Attitudes of the Pre-Service Music Teachers in Turkey

Abstract: <span lang="EN-US">Democracy, a lifestyle as much as it is a form of government, begins to be learned in the family. The youth observe and acquire the democratic attitudes of their parents. The task of passing it on to the new generations and helping them acquire democratic values is the mission of schools, namely teachers. It is a commonly known fact that developmental level of countries shows parallelism with the democratic attitudes of individuals. It is important to understand the democratic percepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 2 publications
0
3
0
1
Order By: Relevance
“…In the study conducted by Çermik (2013), the male pre-service teachers' democratic values were found to be higher than those of the female pre-service teachers. In their study, Bektaş and Kılıç (2011), Chandrakar and Kumar (2016), Eğilmez et al (2018), Güven et al (2014), Saracaloğlu et al (2013), Taş (2018), and Toptaş and Elkatmış (2015) found that pre-service teachers' democratic attitudes do not vary significantly depending on gender. Similarly, Aladağ and Çiftçi (2017), Akar et al (2017), Oğuz (2011), Yazıcı (2011), and Zehir Topkaya and Yavuz (2011) concluded that pre-service teachers' democratic values do not vary significantly depending on gender.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In the study conducted by Çermik (2013), the male pre-service teachers' democratic values were found to be higher than those of the female pre-service teachers. In their study, Bektaş and Kılıç (2011), Chandrakar and Kumar (2016), Eğilmez et al (2018), Güven et al (2014), Saracaloğlu et al (2013), Taş (2018), and Toptaş and Elkatmış (2015) found that pre-service teachers' democratic attitudes do not vary significantly depending on gender. Similarly, Aladağ and Çiftçi (2017), Akar et al (2017), Oğuz (2011), Yazıcı (2011), and Zehir Topkaya and Yavuz (2011) concluded that pre-service teachers' democratic values do not vary significantly depending on gender.…”
Section: Discussionmentioning
confidence: 93%
“…The pre-service teachers' democratic tendencies were found to be not varying significantly depending on father's education level. In the studies conducted by Aydemir and Aksoy (2010); Eğilmez et al (2018); Güven et al (2014); Gömleksiz and Çetintaş (2011);Toptaş and Elkatmış (2015), the pre-service teachers' democratic attitudes were found to be not varying significantly depending on father's education level. These studies support the current study.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Devletin bir yıldan uzun ve kısa vadeli iç borçlanma araçlarına Devlet İç Borçlanma Senetleri (DİBS) adı verilmektedir 102 . Hazine'nin bir yıl ve daha uzun vade ile borçlanma senedi olan devlet tahvilleri 103 esas olarak Hazine ve Maliye Bakanlığı tarafından belirlenen piyasa yapıcı 104 bankalar 105 arasında bir işlem türüdür. Piyasa yapıcı bankalar, devletin gelir elde etmek için ihaleye çıkardığı iç borçlanma senetlerini alarak devlete doğrudan borç vermekte ve birincil piyasayı oluşturmaktadır 106 .…”
Section: B Tasarruf Sahibi Bakımından Değerlendirmeunclassified
“…Enflasyonla mücadele ve döviz kuru politikasını sağlamlaştırmak için ise gelirler politikası uygulanarak ücret ve fiyat artışlarının enflasyon hedefiyle tutarlı olmasının sağlanması, bu hedefi desteklemek üzere enflasyon hızına göre belirlenen döviz kuru çıpası uygulamasına geçilmesi amaçlanmıştır (Hazine ve Maliye Bakanlığı, 1999). Böylece öngörülen programla mali disipline dayalı sıkı maliye politikası ve yalnızca döviz girişleri karşılığında piyasaya Türk lirası enjekte edebilecek daha pasif bir para politikası uygulanması hedeflenmiştir (Eğilmez, 2001).…”
Section: Giriş: Neoliberalizm üZerineunclassified